USE OF FOAM PLASTICS FOR PREVENTING SEASONAL GROUND FREEZING - Priimak,A. I. (1970)
The report describes experimental efforts to install foam plastics in excavations to act as thermal protection against freezing. Trans. of mono. Seasonal Melting and Freezing of Ground in the Northeastern USSR, n.p., n.d., p99-105.